Silver on the tree - Cooper, Susan, 1935- (New York : Aladdin Paperbacks, 2000)
In the Welsh hills Will Stanton, youngest of the immortal Old Ones, joins forces with Merriman, Bran, and the mortal Drew children in a quest through space and time against the powers of evil known as the Dark.
Keywords: Space and time -- Juvenile fiction; Fantasy -- Juvenile fiction; Wales -- Juvenile fiction; Fantastic fiction